Sistem Pendukung Keputusan Pemilihan Supplier Pada PT. Avo Innovation Technology Dengan Metode Simple Addivite Weighting (SAW) - Ahmad Ramadhan; Supatman Supatman (Prodi Sistem Informasi Universitas Dharma Andalas, 2022)
Subjective decision making can lead to errors in supplier selection. In the selection of suppliers, the OEM (Original Equipment Manufacturing) Department has difficulty in choosing suppliers, because many suppliers have submitted offers of cooperation. Therefore, we need a supplier selection decision support system so that the OEM department can determine the appropriate supplier in purchasing products, services and materials. This decision support system uses the SAW (Simple Additive Weighting) method where this method is used to overcome existing problems, because there are many alternatives and criteria that must be considered in supplier selection such as legality, quality management, production capacity, production quality and innovation. From the tests carried out by comparison through Microsoft Excel and the web-based SAW program at PT Avo Innovation Technology using 13 data suppliers to test system performance. It was concluded from the test that the percentage of system performance was 100%, so that this system could be implemented in the company.